Correlation of serum magnesium levels in febrile convulsions in children: a cross sectional comparative study - Addlur, Shalini; Khandelwal, Rohit; Mangajjera, Shivalingappa B.; Mehta, Leeni (International Journal of Contemporary Pediatrics, 2021)
Background: Febrile convulsions is one of the most common type of seizures seen in children. It has been suggested that low serum magnesium (Mg) has occasionally been associated with epilepsy. A positive correlation of the hypomagnesemia with the severity of epilepsy was also found. The present study aimed to estimate the levels of serum magnesium in children with febrile convulsions and to compare serum magnesium levels with normal children. Methods: Fifty patients who were eligible after screening for inclusion and exclusion criteria were included in the study group after a signed written informed consent and 50 controls were also taken. A detailed history, clinical examination and these investigations were done – complete blood count (CBC) (Hb, DC and ESR), serum calcium, serum magnesium, serum electrolytes, random blood sugar and cerebrospinal fluid (CSF) analysis. Results: The serum magnesium level was normal in 45 patients (90%) with febrile convulsions, low levels in 4 cases (8%) and high levels seen in 1 case (2%). Serum magnesium levels were normal in all 50 controls. In this study, the serum magnesium levels has got no correlation in patients with febrile convulsion. So, routine magnesium supplementation need not be prescribed in normal subjects to prevent febrile convulsions. Conclusions: Routine measurement of serum levels of Mg, glucose and calcium are warranted in subject with febrile convulsions. However, large prospective studies are further required in future to establish the correlation of serum Mg and febrile convulsions so that a standard guidelines can be set up which could be followed universally.